Treatment of clavicle fracture using wise lock clavicle hook plate and wise lock superior anterior clavicle plate - Thakur, Soni; Sharma, Shagun; Kumar, Mohit; Rawat, Pooja; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2019)
Background: Clavicle fracture is common in adults associated with high non-union rate and post-operative complications. The aim of this prospective study was to reduce the postoperative complications in clavicle fracture (Type 15-A2 and 15-B1) by using wise lock plates (manufactured by Auxein Medical Private Limited). Methods: In this prospective study of 25 patients (11 patients had 15-A2 fracture, 14 patients had 15-B1 fracture) recruited with one year follows up period followed by physical exercises after one month of the surgery. The fractures were treated with two different plates: 3.5 mm wise lock clavicle hook plate and 3.5 mm wise lock superior anterior clavicle plate. X-ray was used to check the union, non-union. Functional outcome of the patients were assessed by the visual analogue scale (VAS) score at post-operative follow up at 4 weeks, 12 weeks, 6 months and 1 year. Results: Postoperative outcome was good with none of the patients showing non-union or delay in the union of fracture site. The encountered complication registered were residual pain which was mild (4 cases), and hypoesthesia (2 cases). Conclusions: Osteosynthesis of clavicle fracture with 3.5 mm diameter locking plates attributed as superior, anterior and hook plating system showed excellent results with low rate of complications.